Interpersonal Communication Processes between Students, Caregivers of Boarding School, and Boarding School Environments in Building the Self Concept - Maulia, Putri; Budi Lestari, SU, Dr. Dra. Sri (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2017)
In a family, interpersonal communication processes take place in nurturing and controlling against the behavior of their children. Now, many parents who choose to educate his children in boarding schools and they hopes their children can have a religious knowledge as well as a good general science, have a good character, and have a positive self-concept if educated in the boarding school. This research using a qualitative approach, aims to describing interpersonal communication processes between students, caregivers of boarding school, and boarding school environments in building the self concept. This research uses interpretive paradigms and phenomenological methods. Subjects in this research were two students and two caregivers of Pondok Pesantren Al Muqoddasah, East Java. The underlying theory is symbolic interaction theory and self concept by George Herbert Mead. The results show that the caregiver has intimacy with his students by always communicating, devoting affection, empathy, attention, and feelings of equality among them, especially with students who are still children. The intimacy that exists among the students is also one of the reasons they feel happy and comfortable life in the boarding school. This familiarity is established because of the openness, the similarity of hobbies, sense of the same fate, and the interdependent feelings that makes the student would not feel lonely and lack the affection from their parents. Students also feel comfort and can adapt to boarding school environments easily, because the boarding school environment is considered to have a role in the development of their self-concept, where the values, culture, and norms that are taught can change the behavior and habits of students to be better. The process of developing student selfconcept is also affected by the way of caregivers in nurturing and controlling his students. Caregivers who always give positive assessments and nurturing his students with a secure attachment style helps the student in the process of building a positive self-concept. Meanwhile, caregivers who always give negative assessments and nurturing her students with fearful attachment style or anxious attachment style will damage the confidence and self-esteem of the students so his self-concept becomes negative. Student builds his self-concept based on interaction with caregiver, fellow student, and his boarding school environments. Self-concept that will provide an important motive for student behavior.